1980
DOI: 10.1002/eji.1830101116
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mitogen‐induced peripheral B cell differentiation by soluble Fcγ receptors released from lymphocytes

Abstract: Soluble receptors for FcIgG released from unstimulated human peripheral blood lymphocytes were isolated by affinity chromatography on Sepharose 4B-IgG. This material was shown to interfere with the differentiation of peripheral blood B cells into Ig-secreting cells in cultures stimulated with pokeweek or Nocardia opaca extracts. Neither cell viability nor [3H]thymidine incorporation were altered, but the number of Ig-containing cells and that of Ig-secreting cells were decreased. These effects were dose-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In regard to negative signals, T suppressor cells that preferentially inhibited IgA (4), IgE (5), and IgG2a and IgG2b (6) plaqueforming cells (pfc) were reported. Immunoglobulin-binding factor(s) [IBF(s)] that inhibit the differentiation of B cells to pfc have been described (7,8). Further studies of this factor by Fridman et al (9) demonstrated that IBF is the soluble form of Fcy receptor expressed on a T-cell subset.…”
mentioning
confidence: 99%
“…In regard to negative signals, T suppressor cells that preferentially inhibited IgA (4), IgE (5), and IgG2a and IgG2b (6) plaqueforming cells (pfc) were reported. Immunoglobulin-binding factor(s) [IBF(s)] that inhibit the differentiation of B cells to pfc have been described (7,8). Further studies of this factor by Fridman et al (9) demonstrated that IBF is the soluble form of Fcy receptor expressed on a T-cell subset.…”
mentioning
confidence: 99%
“…FcyR on inflammatory cells in peripheral blood are involved in several important patho-physiologic phenomena: binding and phagocytosis of antibody-coated particles, antibody dependent cytotoxicity, the release of soluble mediators of inflammation such as prostaglandins and hydrolytic enzymes and suppression of mitogen-induced B lymphocyte differentiation and Ig production (15,27). Our studies indicate that FcyR are generally expressed on cells in inflamed tissue.…”
Section: Discussionmentioning
confidence: 64%
“…Several cell types may eontribute to the binding of EA and IgG immune complexes to gingival infiltrates, most likely B lymphocytes and monocytes/macrophages, although NK cells and possibly suppressor/ eytotoxic T cells may also eontribute. These receptors may be involved in several pathophysiologic phenomena: binding and phagocytosis of antibody-coated particles, antibody-dependent cytotoxicity, the release of soluble mediators of inflammation such as prostaglandins and hydrolytic enzymes and suppression of mitogen-induced B cell differentiation (Zuckerman & Douglas 1979, Le thi Bich-Thuy et al 1980.…”
Section: Discussionmentioning
confidence: 99%